RETROSPECTIVE STUDY OF MALARIA PREVALENCE IN SELECTED HOSPITALS IN ZARIA, NIGERIA - Ibrahim, Abdulhamid B.; Kogi, E. (FUDMA JOURNAL OF SCIENCES, 2021)
A retrospective study of laboratory records in selected hospitals in Zaria was carried out to determine the trend of malaria prevalence between 2001 and 2005. Data was obtained from the following selected hospitals: St Lukeâ€™s Anglican Hospital, Wusasa, Salama Infirmary, Saidu Dange railway Hospital and Sick Bay, Ahmadu Bello University, Main campus, Samaru. The selection of the hospitals was based on their geographical location and sizes. The prevalence was consistently high over the years; 2001â€“44.1%, 2002â€“59.45%, 2003â€“59.35%, 2004â€“58.30% and 2005â€“64.25%. There was no significant difference (P>0.05) between malaria infection in males and females. Infection rates were significantly higher in children than adults (P<0.05) in all hospitals sampled except Salama Infirmary. Sick Bay in the main campus, Samaru had the least prevalence consistently over the five years period â€“ 2001-27.0%, 2002-26.3%, 2003-21.8%, 2004-25.9% and 2005-33.2%. No clear seasonal variation over the years was observed. The study clearly showed consistent high prevalence over the five years period. Record keeping was useful as it provided data bur devoid of specific ages of attendees. Specific ages of hospital attendees rather than â€œchildrenâ€ or â€œadultsâ€ should be recorded and other demographic variables such as occupation and other socio-economic proxies should be included in laboratory record books